Quality of Education : The Gateway to Employability - Akhtar, Shamshad (World Bank, Washington, DC, 2012)
The Luxor Education Roundtable (March 19-20, 2010) on the quality of education: the gateway to employability was jointly organized between Minister of Investment Mahmoud Mohieldin of Egypt and the World Bank. The round table is a direct response to a request from the Government of Egypt (GoE) to identify and share best practices in the development of sound education systems around the world. The objective is to enrich the current debate among Egyptian decision makers on how to improve the quality of education so that it contributes more effectively to the country's future economic development.